Analisis Kualitas Pelayanan pada Restoran XYZ dalam Rangka Mengukur Kepuasan Pelanggan - Stella Stella; Eko Harry Susanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
The good quality of the service is one of important aspect for any restaurants, especially for various old restaurants in Jakarta to stay in the completion in this industry. In this research, the researcher used XYZ Restaurant as the object of this research to give feedback to XYZ Restaurant to know whether their service quality has already met their customers' expectation, so that XYZ Restaurant can keep competing in this global competition. XYZ Restaurant is Chinese Food restaurant that can be said has been long enough in this industry, We live in the era where food and restaurant business is continuously expanding in Indonesia, whether in a similar business or not, from traditional as well modern. Writer used service quality for the method in this research and dimensions that measured are tangibility, reliability, responsiveness, assurance and empathy, in which compares perception or what customer’s feels compared with what customer expect from the dimensions. From the calculations performed by the writer, overall, XYZ Restaurant score of service quality is negative it means perception score is lower than expectation score. Therefore, XYZ Restaurant need to fix dimension of Tangibility and Assurance, because is lower than customer’s expectation. Meanwhile for reliability dimension, Responsiveness dimension and Empathy dimension have to be in keep because its already higher than customer expectation. Overall, XYZ Restaurant need to fix their service quality because their service is haven’t meet customer’s expectation.